Związki romantyczne młodzieży z zaburzeniami psychicznymi - Kubiak , Hanna (Studia Edukacyjne, 2022)
The article deals with the issue of romantic relationships experienced by adolescents with mental disorders. It presents the importance of participation in romantic relationships for the development of adolescents and how the process can be disrupted if the adolescents experience mental disorders. The difficulties concern both entering pre-intimate relationships as well as functioning in them. The main obstacles in this situation are related to the self-esteem of adolescents with mental disorders and the phenomenon of labeling them. The support system around young people with mental health problems consists not only of parents and teachers, but also of psychotherapists, educators and psychiatrists. The text ends with psycho-pedagogical postulates.